Peningkatan Motivasi dan Hasil Belajar Materi Medan Magnet Menggunakan Metode Cooperative Learning Tipe Jigsaw pada Siswa Kelas X TAV 3 SMK Negeri 1 Adiwerna Semester Genap Tahun Pelajaran 2017/2018 - Musriyah Musriyah (Jurnal Penelitian Pembelajaran Fisika, 2018)
This research is motivated by the reality at Adiwerna Tegal 1 State Vocational School, that the results of learning the magnetic field class X TAV 3 have not achieved the expected results. The first daily test results were still low, still below the ideal classical completeness criteria set at 80%, and individual learning outcomes above KKM of ≥ 70 or individual absorption of 70%. The method in collecting data is a test technique used to measure students 'comprehension in the form of learning outcomes and observation techniques carried out collaboratively to record students' motivation in learning and to know the progress of the learning process from cycle to cycle. From the results of data analysis, it is stated that: 1) Initial conditions, that classical absorption power which is the learning outcomes of all students only reached 55.56% means that it is under the classical completeness that has been set at 80% (ideal conditions). 2). In Cycle 1, classical absorption reached 72.22% which means it was still under class completeness. 3). In Cycle 2, the classical absorption capacity reached 86.11% above the class completeness which was set at 80%. From the results of the study it can be concluded that there is an increase in motivation and learning outcomes of magnetic field material by applying the cooperative jigsaw type learning method to class X TAV 3 of Adiwerna Tegal 1 State Vocational School of the school year 2017/2018.